Editorial Note Vol.3 - KC, Fatta Bahadur (Nepalese Journal of Insurance and Social Security, 2020)
The first issue of Journal of Insurance and Social Security (NJISS) was published in 2018, second issue in 2019 and the third issue is in your hand. The Editorial Board expresses words of gratitude to all authors, reviewers, advisors and readers for their valuable contribution. In coming days too, we expect such invaluable support and encouragement from our valued personalities so that we will be able to publish the journal frequently maintaining standard of the journal with the international repute. The third issue has incorporated six articles that have been selected out of the dozens of manuscripts. We state the words of gratefulness to all the contributors who showed affection and trust over the NJISS and sent these papers. The Editorial Board requests to all prospective contributors to upload their manuscripts following the general guidelines of the journal. Current issue is also known as social health insurance issue since out of six articles, four are related to government run health insurance schemes while one is related to life insurance lapse and another one is related to insurance education. Nepalese insurance industry can be divided under four segments: privately owned companies run commercial insurance, Social Security fund led social insurance, health insurance board led social health insurance and deposit and credit guarantee fund. The articles published in this issue cover the topics under the commercial insurance and social health insurance. The journal always welcomes the critical review papers on up-to-date subjects on any of the topics in the area of risk, insurance, social security, microfinance, pension, annuity and the related disciplines. Prof. Fatta Bahadur KC Editor-in- Chief NJISS